Pengembangan bahan ajar Pendidikan Agama Islam tema menyebutkan sifat ja’iz bagi Allah SWT., menggunakan model snowball throwing siswa kelas IV di SDN Miji 2 Kota Mojokerto - Padi, Achmad (Ta'dibia: Jurnal Ilmiah Pendidikan Agama Islam, 2017)
The purpose of this research development is: 1) To find out the teaching materials of Islamic Religious Education theme mentions the nature of ja'iz for Allah SWT, using the model of snowball throwing fourth grade students in SDN Miji 2 Mojokerto according to expert 2) To know the teaching materials of Religious Education Islam theme mentions the nature of ja'iz for Allah SWT, using the model of snowball throwing fourth graders in SDN Miji 2 Kota Mojokerto according to teacher 3) To know the teaching materials of Islamic Religious Education theme mentions the nature of ja'iz for Allah SWT, using the model of snowball Throwing can improve the learning of fourth grade students in SDN Miji 2 Kota Mojokerto. Product teaching materials Islamic Religious Education theme mentions the nature of ja'iz for Allah SWT., Using this snowball throwing model has been perfected based on analysis of trial data. Based on the steps that have been implemented can be concluded as follows. 1). Product teaching materials Islamic Religious Education theme mentions the nature of ja'iz for Allah SWT., Using the model of snowball throwing fourth graders in SDN Miji 2 Mojokerto City according to experts scored 3.95 with enough category. 2) The teaching materials of Islamic Religious Education theme mentioned the nature of ja'iz for Allah SWT, using the model of snowball throwing of fourth grade students in SDN Miji 2 Kota Mojokerto according to the teacher obtained score of 3.90 with enough category 3) The teaching material product of Islamic Religious Education The theme mentions the nature of ja'iz for Allah SWT., Using the model of snowball throwing can improve the learning of fourth grade students in SDN Miji 2 Kota Mojokerto with the average choice of students is 3.61, it is categorized Enough with standard 0.30 intersection.